O diálogo como comunicação e co-elaboração : possibilidade de intervenção psicossociais - Sabiá, Pácifer Maia (2012)
The objective of this research was to characterize the dialogue with possibilities of psychological attention to the understanding of psychosocial processes in the Center for Psychosocial Care (CAPS) Casa Verde, and, in the Hospital Escola Portugal Ramalho (HEPR) and, Universidade Estadual de ciências da Saúde de Alagoas (UNCISAL .) It is a genre of practice consistent with the principles of psychosocial thinking of Paulo Freire, assuming inter subjective relations that transcend its immediacy and affect other dimensions of social life. The research is justified by the opportunity to present and characterize a new praxis of psychological care that brings together, at the same time, the participation of all social actors who moves in the institution, focused on the search for understanding of many issues that cross their everyday lives psycho pedagogical, subjective and institutional - and required ethical and political positions, in addition to being able to contribute, even more, to think of this modality in other social contexts. In this perspective, while going deeper into psychological conception of subjectivity in historical and cultural of Freire‟s, we also approach the thoughts of the social psychologist Fernando L. González Rey, considering the dialogue as an enabler of strategy inherent in clinical psychological care psychosocial. This is a qualitative research, in a psychosocial perspective, and interventional, as the analysis of the implications of those that implied the field of intervention allows access to the subjective processes of institutional and social actors involved. The subjects were chosen intentionally, considering the participation of users, trainees, visitors and staff of Casa Verde Caps in groups Dialogue. There was not a predetermined number of participants, given that the resource used - group work - allowed a free and voluntary participation of the stakeholders. There were six meetings of the Dialogues, a regular weekly one-hour each groups, and the issues discussed related to the motivations, needs and interests of the participants in the group itself, with no defined topics. The development of work groups with the presence of a co-facilitator, aiming to share with the researcher's perceptions and interventions made in groups. In addition to group meetings, an interview was conducted with the co-facilitator, to evaluate the possible resonances of group work for those who participated. It also built a diary to record aspects and phenomena related to work, and do not contemplated in the group meetings. For the process of understanding the material, we use the methodology proposed by González Rey, considering the following steps: the production of indicators for the analysis of the themes emerging in dialogue groups from the construction of the units of meaning; synthesis of core meaning of group meetings, analysis of themes emerged in the interview from the core meaning, and observations made by field, taken on two forms of presentation: the group and the institution. The analysis of this material showed us that the group developed a dialogue ethical / political, psychosocial and educational in its production of culture and knowledge, contributing to the development of suffering and the issues presented in the context of the production of a critical subjectivity